THE ROLE OF RESEARCH WORKSHOPS IS TO INCREASE PUBLICATION INTEREST IN ACCREDITED JOURNALS - Muhfiatun Muhfiatun; Dwi Marlina Wijayanti; Prasojo Prasojo; Lailatis Syarifah; Sofyan Hadinata (Journal of Islamic Economy and Community Engagement, 2021)
This study aims to determine the interest of final year students who are completing their final project to make publications in reputable journals. At present, 9 criteria accreditation requires a lot of publications from students while the climate of publication of student work is still not well formed. Therefore, activities and policies are needed to build a culture of publication. Research workshops are one way to encourage students to make publications. This study uses final year students who are finishing their final assignments as respondents/ workshop participants. The goal is that the results of their final project can be published directly in a reputable journal. The results showed that after attending the workshop, the majority of respondents gave positive responses related to the workshop activities and had a high enough interest to do the publication. The results of this study have practical implications for policy makers to regularly conduct research workshops for students.